Students’ learning experience in a mixed reality environment: drivers and barriers - John, Blooma (2022)
Mixed reality technologies have the potential to provide students with an effective learning experience by bridging the gap between the digital and physical world. Mixed reality enables the user to see their real-world surroundings with virtual features overlayed in order to create a digitally enhanced experience. As we strategically move towards large-scale integration of mixed reality technologies to maximize the learning affordances in the future, there is a need to understand the drivers of and barriers to students’ learning in a mixed reality environment. We present in this paper a multi-site case study to evaluate the feedback from 223 students on their learning experiences after using Microsoft HoloLens, a mixed reality device, in their classroom. While we found that interactivity, immersion, and presence are the main drivers, the key barriers identified were difficulty using the device, accessibility issues, and the lack of flexibility. Affordances and fatigue are the two themes that evolved in this study. We recommend three design principles that will contribute toward designing mixed reality technologies to effectively build new embodied learning environments.